Improper arterial catheter blood sampling method affects hemoglobin test results: A cautionary tale - Jinle Wang; Huihui Jiang; Qingqing Bi; Kegang Tian; Xiaofeng Mu; Lei Zhang (Journal of International Medical Research)
Arterial catheter blood sampling is widely used among critically ill patients to minimize repeated punctures; however, improper techniques may lead to misleading laboratory results. This case report presents a clinically significant hemoglobin discrepancy observed between blood gas analyzer and automated hematology analyzer during arterial catheter sampling in a patient with cerebral infarction. After catheter placement, the interplatform hemoglobin discrepancy reached 13 g/L despite prior concordance. The discordance was attributed to pre-analytical errors, including inadequate discard volume (4–5 mL) of heparinized saline–contaminated blood, which causes sample dilution. This case underscores that catheter sampling protocols must rigorously focus on dead space clearance to prevent artifactual hemoglobin variations. Such vigilance is particularly critical in hemodynamically unstable patients, in whom erroneous values may directly impact transfusion decisions. Adherence to evidence-based discard volume guidelines, with protocol tailoring based on individual patient factors, constitutes an essential safeguard for test accuracy in critical care settings.